Investigating the influence of drying temperature on the flavonoid profile, quercetin content, and antioxidant activity in dayak onion - Arsianti, Rika Wahyuni; Argo, Bambang Dwi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
As a traditional medicinal plant rich in flavonoids, Dayak onion (Eleutherine bulbosa) has great potential as a functional food. However, its high water content requires a proper drying process to maintain its bioactive compounds. This study evaluated the effects of oven drying temperatures 40°C, 50°C, and 60°C on the total flavonoid content (TFC), quercetin levels, and antioxidant activity of Dayak onion. Samples were dried to a target moisture content of 12% and analyzed using UV-Vis spectrophotometry, HPLC, and the DPPH method. The results showed a positive linear relationship between drying temperature and phytochemical quality. 60°C was the most effective condition, increasing TFC from 45.05 mg/L to 101.42 mg/L (2.25-fold), quercetin levels from 9.13 ppm to 17.51 ppm (1.91-fold), and significantly increasing antioxidant activity (decrease in IC₅₀ value). Thus, controlled drying at 60°C is an effective method to improve the quality and functional value of Dayak onions.